Preparation of Co–Gr Nanocomposites and Analysis of Their Tribological and Corrosion Characteristics - Raghav, G.R.; Balaji, A.N.; Muthukrishnan, D.; Sruthi, V. (Металлофизика и новейшие технологии, 2018)
This work summarizes the tribological and corrosion behaviour of Co–Gr nanocomposites. The Co–Gr nanocomposites are synthesized using high-energy ball mill and compacted into cylindrical pellets by hydraulic pressing.